(3QSGdI aj CeQ HbGA GdfaSs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg Cgd cd MeO jchf dg hQZHI Cf jchf Zdjg hJhcd Cf jchf Ydjg hKbI Cf jchf Hg hHYO agPg QSGdI YedJgG HGSe HYV GdNdU ef GdGNhGf eTJedI Ydi eN eG JDOi Edjg GdHQGgjf ef MGd GdfaS s
(3BNQgG (B:s
(3hef jchf HYOge eKdge ai GdfaS Yf ZhGeV hGVY GdQeR hJChjdg Cf QeRjg hHSW Gdbhd GdhLjR ajg hCf CbJUQ Ydjg hLYdJ Gddg JYGdi NUeg Yfi hgh GdeSFhd HGdJhajb Cf jfYe Hg GdMb hCf jgOi Edjg hdg GdMeO Ydi cd MGd hUdhGJg Ydi GdeUWajf ef YHGOg Je GdcJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3QVGQGeHhQ (B(2955(3)) s
Keywords: (3GdadSaI hGdefWbs